2019
DOI: 10.2298/abs181207013c
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA ameliorates acute lung injury by inhibition of the NLRP3 inflammasome

Abstract: Tanshinone IIA is the phenanthrenequinone derivative extracted from the perennial plant Salvia miltiorrhiza Bunge (red sage). We investigated whether inhibition of the nucleotide-binding oligomerization domain (NOD)-like receptor family protein 3 (NLRP3) inflammasome mediates the protective effect of tanshinone IIA in acute lung injury (ALI) induced in rats by oleic acid (OA) injection. Compared with the control treatment, OA injection induced pulmonary histological impairment, increased the lung wet/dry weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is possible that Tan IIA could enhance the expression of Sirt1, thereby promoting cellular p65 protein deacetylation, inhibiting NF-kB transcriptional activation, then inhibit the NF-kB mediated inflammatory process ( Quan et al, 2019 ). Amelioration of acute lung injury by Tan IIA can also inhibit proinflammatory factors by inhibiting the expression of TRPM7 and reducing calcium influx in lung interstitial macrophages ( Li J. et al, 2018 ), as well as preventing nucleotide-binding oligomerization domain (NOD)-like receptor family protein 3 (NLRP3) inflammasome activation ( Chen T. et al, 2019 ).…”
Section: Respiratory Systemmentioning
confidence: 99%
“…It is possible that Tan IIA could enhance the expression of Sirt1, thereby promoting cellular p65 protein deacetylation, inhibiting NF-kB transcriptional activation, then inhibit the NF-kB mediated inflammatory process ( Quan et al, 2019 ). Amelioration of acute lung injury by Tan IIA can also inhibit proinflammatory factors by inhibiting the expression of TRPM7 and reducing calcium influx in lung interstitial macrophages ( Li J. et al, 2018 ), as well as preventing nucleotide-binding oligomerization domain (NOD)-like receptor family protein 3 (NLRP3) inflammasome activation ( Chen T. et al, 2019 ).…”
Section: Respiratory Systemmentioning
confidence: 99%
“…Chen and coworkers reported that a phenanthrenequinone isolated from Salvia miltiorrhiza Bunge (Lamiaceae), Tanshinone IIA, suppressed the nucleotide-binding oligomerization domain-like receptors pyrin domain-containing protein 3 (NLRP3), as an inflammatory signaling pathway, at 10 mg/kg i.v. in rats, thereby reducing the oleic acid-induced lung injury ( Chen T. et al, 2019 ). Also, emodin, an anthraquinone found in different laxative plants such as Rheum rhabarbarum L. (Polygonaceae), showed protective effects on LPS-lung injury via activating autophagy pathways at 20 mg/kg i.p.…”
Section: Phytochemicals As Potential Agents For Coronavirus-associatementioning
confidence: 99%